2021
DOI: 10.1038/s41598-020-80294-1
|View full text |Cite
|
Sign up to set email alerts
|

Exosite inhibition of ADAMTS-5 by a glycoconjugated arylsulfonamide

Abstract: ADAMTS-5 is a major protease involved in the turnover of proteoglycans such as aggrecan and versican. Dysregulated aggrecanase activity of ADAMTS-5 has been directly linked to the etiology of osteoarthritis (OA). For this reason, ADAMTS-5 is a pharmaceutical target for the treatment of OA. ADAMTS-5 shares high structural and functional similarities with ADAMTS-4, which makes the design of selective inhibitors particularly challenging. Here we exploited the ADAMTS-5 binding capacity of β-N-acetyl-d-glucosamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…These findings suggest that ADAMTS enzymes and related pathways may be attractive therapeutic targets and further investigation is warranted. In support of these findings a number of antibodies and small molecule inhibitors (for example GSK2394000, GSK2394002, 237-53, sugar-based arylsulfonamide 4b, and Agg-523) are currently available and in clinical and preclinical trials that can be used to target ADAMTS enzymes (Dancevic and McCulloch, 2014;Larkin et al, 2015;Santamaria et al, 2015;Shiraishi et al, 2016;Balchen et al, 2018;van der Aar et al, 2018;Malemud, 2019;Santamaria and de Groot, 2019;Santamaria, 2020;Santamaria et al, 2021). It should be noted however that over-expression of ADAMTS enzymes may also improve disease outcomes (McMahon et al, 2016).…”
Section: A Disintegrin-like and Metalloproteinase With Thrombospondin Motifsmentioning
confidence: 94%
See 1 more Smart Citation
“…These findings suggest that ADAMTS enzymes and related pathways may be attractive therapeutic targets and further investigation is warranted. In support of these findings a number of antibodies and small molecule inhibitors (for example GSK2394000, GSK2394002, 237-53, sugar-based arylsulfonamide 4b, and Agg-523) are currently available and in clinical and preclinical trials that can be used to target ADAMTS enzymes (Dancevic and McCulloch, 2014;Larkin et al, 2015;Santamaria et al, 2015;Shiraishi et al, 2016;Balchen et al, 2018;van der Aar et al, 2018;Malemud, 2019;Santamaria and de Groot, 2019;Santamaria, 2020;Santamaria et al, 2021). It should be noted however that over-expression of ADAMTS enzymes may also improve disease outcomes (McMahon et al, 2016).…”
Section: A Disintegrin-like and Metalloproteinase With Thrombospondin Motifsmentioning
confidence: 94%
“…pathology Li et al (2017) May contribute to increased mortality Viasus et al (2011), Ni et al (2019), Ye et al (2020), Zhou et al for increased viral transmission Davies et al (2009), Arulkumaran et al (2020), Ng et al (2020), Al Lawati et al (2021) ECM manipulation Emerging Unknown Newly identified roles for zinc proteases in virus infection. Wu et al (2007), McMahon, et al (2016), Rojas-Quintero et al (2018), Boyd et al (2020)New field of researchin vitro, in vivo and human ex vivo inhibitionLarkin et al (2015),Santamaria et al (2015) May lack binding specificitySantamaria et al (2021) …”
mentioning
confidence: 99%
“…Additionally, when testing possible synergistic effects of combining both ADAMTS4- and ADAMTS5-inhibiting mAbs, ADAMTS5 appeared to be the dominant ADAMTS protease mediating cartilage degeneration in human cartilage explants or in primary human chondrocytes. As an alternative to mAbs, an ADAMTS5 exosite inhibitor based on a glycoconjugated arylsulfonamide was developed recently, which showed selectivity over ADAMTS4 and inhibited both, versican and aggrecan cleavage ( Santamaria et al, 2021 ). It will be interesting to see how these inhibitors will perform in vivo since both, versicanase and aggrecanase activity, are blocked, or if exosite inhibitors can be developed that can discriminate between versican and aggrecan recognition.…”
Section: Inhibitors Of Adamts Proteasesmentioning
confidence: 99%
“…M6495 was recently out-licensed to Novartis, and phase II trials are expected. Targeting exosites outside of the metalloproteinase active site is another promising approach, recently shown to enable development of an inhibitor with high selectivity for ADAMTS-5 over ADAMTS-4 [37].…”
Section: Inhibiting Adamts Activitymentioning
confidence: 99%